2020
DOI: 10.1177/0036850420950122
|View full text |Cite
|
Sign up to set email alerts
|

Wear analysis of finger locks with different design parameters for landing gear

Abstract: The finger lock in the retractable actuator of the landing gear will wear during repeated unlocking and locking. Therefore, the effects of six parameters including the material of the finger lock, the length of the finger lock, the diameter of the finger lock, the number of petals, and the angle of the fingertip on the unlocking force after 500 unlocking cycles are researched. Archard wear theory was performed to obtain the unlocking force after wear and the influence of six key parameters on the unlocking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Aircraft are a reliable, economical, and fast means for carrying people and goods, thus playing an important role in transportation [ 1 , 2 , 3 ]. As a result, the analysis of their structural parts and the related failure is pertinent as the system plays an important role as a bridge between the aircraft fuselage and the wheel brake system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aircraft are a reliable, economical, and fast means for carrying people and goods, thus playing an important role in transportation [ 1 , 2 , 3 ]. As a result, the analysis of their structural parts and the related failure is pertinent as the system plays an important role as a bridge between the aircraft fuselage and the wheel brake system.…”
Section: Introductionmentioning
confidence: 99%
“…After calculating the equivalent stress and contact stress after interference fit, it was found that the wear range increased for larger interference values. Hou et al [ 1 ] studied the effects of six parameters—lock material, lock length, lock diameter, number of petals, and fingertip angle—on the unlocking force after 500 unlocks. However, the influence of the surface treatment of the base material on the axial force requires further investigation.…”
Section: Introductionmentioning
confidence: 99%